QORAQLPOG’ISTON SHAROITIDA MAALLIY QORAMOLLARDA TEYLERIOZ KASALLIGINING UCHRASHI - Arziyev X.Y.; Arislanbekov I.A.; Abatbaeva A.M. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article describes the incidence of Tayloriosis in Karakalpakstan, its economic damage to farms, its course, and the results of testing blood samples from farm animals.